Дослідження впливу концентрації завислих часток у розчині на ефективність їх флокуляції - Босюк, Альона Сергіївна; Шестопалов, Олексій Валерійович; Мельник, Ігор Іванович (ФОП Яроченко Я. В., 2024)
The effectiveness of the process of clarifying water from undeposited suspended particles after the introduction of special reagents such as flocculants and coagulants was investigated. It was found that the use of these chemicals promotes the formation of large flocs, improving clarification and contributing to the effective removal of invisible particles from water.
Keywords: реагенти; стічні води; концентрація завислих часток; очищення стічних вод; флокуляція; коагуляція